AN OVERVIEW OF HIV TREATMENTS: WHAT TO START - Vinci Mizranita (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2016)
Combinations of HAART using 2 NRTIs plus NNRTIs or PIs (zidovudine, abacavir or tenofovir plus lamivudine, or emtricitabine plus tenofovir) are preferred treatment of HIV infection internationally and in Australia.Some antiretroviral should not be combined due to overlapping toxicities and potential viral antagonism (e.g. Atazanavir + indinavir, didanosine + stavudine). The challenges for treating HIV infection will be to reduce adverse effects, drug resistance, and increased options for treatment-experienced patients (HIV patient with previously treated using ARV).